Cosmic ray astroparticle physics: current status and future perspectives. Issue Volume 12:Issue S331(2017) (17th October 2017) - Donato, Fiorenza
Abstract: The data we are receiving from galactic cosmic rays are reaching an unprecedented precision, over very wide energy ranges. Nevertheless, many problems are still open, while new ones seem to appear when data happen to be redundant. We will discuss some paths to possible progress in the theoretical modeling and experimental exploration of the galactic cosmic radiation.